Essays on fiscal illusion - Pinar, Abuzer (1998)
The objective of this study is to examine the relationship between taxation and public spending in the UK, utilising public choice theories that the level of government spending should reflect voter-taxpayer's demand for public goods. Such theories argue that certain features of the tax structure affect voter's perceptions of their tax burden so that they underestimate how much they are paying for public goods. Fiscal illusion is investigated as a key issue in a time series analysis of general government expenditures, and a cross-section analysis of local government spending. Also survey data from British Social Attitudes is employed to analyse the relationship between tax perceptions and preferences for public spending.